Dll1 haploinsufficiency causes brain abnormalities with functional relevance - Arzate, Dulce-María; Valencia, Concepción; Dimas, Marco-Antonio; Antonio-Cabrera, Edwards; Domínguez-Salazar, Emilio; Guerrero-Flores, Gilda; Gutiérrez-Mariscal, Mariana; Covarrubias, Luis (Frontiers in Neuroscience, 2022)
Introduction The Notch pathway is fundamental for the generation of neurons during development. We previously reported that adult mice heterozygous for the null allele of the gene encoding the Delta-like ligand 1 for Notch (Dll1lacZ) have a reduced neuronal density in the substantia nigra pars compacta. The aim of the present work was to evaluate whether this alteration extends to other brain structures and the behavioral consequences of affected subjects. Methods Brains of Dll1+/lacZ embryos and mice at different ages were phenotypically compared against their wild type (WT) counterpart. Afterwards, brain histological analyses were performed followed by determinations of neural cell markers in tissue slices. Neurological deficits were diagnosed by applying different behavioral tests to Dll1+/lacZ and WT mice. Results Brain weight and size of Dll1+/lacZ mice was significantly decreased compared with WT littermates (i.e., microcephaly), a phenotype detected early after birth. Interestingly, enlarged ventricles (i.e., hydrocephalus) was a common characteristic of brains of Dll1 haploinsufficient mice since early ages. At the cell level, general cell density and number of neurons in several brain regions, including the cortex and hippocampus, of Dll1+/lacZ mice were reduced as compared with those regions of WT mice. Also, fewer neural stem cells were particularly found in the adult dentate gyrus of Dll1+/lacZ mice but not in the subventricular zone. High myelination levels detected at early postnatal ages (P7–P24) were an additional penetrant phenotype in Dll1+/lacZ mice, observation that was consistent with premature oligodendrocyte differentiation. After applying a set of behavioral tests, mild neurological alterations were detected that caused changes in motor behaviors and a deficit in object categorization. Discussion Our observations suggest that Dll1 haploinsufficiency limits Notch signaling during brain development which, on one hand, leads to reduced brain cell density and causes microcephaly and hydrocephalus phenotypes and, on the other, alters the myelination process after birth. The severity of these defects could reach levels that affect normal brain function. Therefore, Dll1 haploinsufficiency is a risk factor that predisposes the brain to develop abnormalities with functional consequences.